ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVEINING TAHUN 2019-2021 - Fitriya, Heni; Karnadi, Karnadi; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2023)
The aim of this research is to determine the influence of Ownership Structure and Dividend Policy on Company Value with Debt Policy as an intervening variable in LQ45 companies on the Indonesia Stock Exchange for the 2019-2021 period. The population of this research is all 45 LQ45 companies registered on the IDX. The sampling technique in the research used purposive sampling so that 10 data analysis samples were obtained. Data analysis and hypothesis testing in this research used the Smart PLS 3.0 application. The results of this research indicate that Ownership Structure and Dividend Policy have a significant negative effect on Debt Policy, Ownership Structure does not have a significant effect on Company Value. Ownership Structure and Debt Policy have a significant negative effect on Company Value, and Dividend Policy has a significant positive effect on Company Value. Ownership Structure and Dividend Policy do not have a significant effect on Company Value through Debt Policy.